USING MODERN TEACHING METHODS AND INNOVATIVE TECHNOLOGIES IN EDUCATIONAL PROCESS - Кулаєць, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Teacher’s activity of higher medical education and his educational technology that he uses should ensure the primarily formation of professionally competent, successful, purposeful specialist. Educate the highly qualifictd person can only teacher, that is the teacher who is able to self-organization and self-improvement. Modern teaching methods are designed to promote rethinking of relationship teacher and student between psychologically comfortable learning environment in which students feel their impact, intellectual independence, that makes more efficient the process of learning – that is why this subject is very relevant issue today. The article deals with the problem and the need to use modern methods of teaching in higher medical educational establishments, which must be understood in accessible form,effective, and take into account the individual characteristics of the student to match his age and abilities to perform the following functions: learning, developing educational, training, motivational, corrective control.